Astragaloside IV Alleviates Brain Injury Induced by Hypoxia via the Calpain-1 Signaling Pathway - Yan Meng; Shengxue Yu; Fang Zhao; Yu Liu; Yue Wang; Siqi Fan; Yuhong Su; Meili Lu; Hongxin Wang (Neural Plasticity)
Long-term hypoxia can induce oxidative stress and apoptosis in hippocampal neurons that can lead to brain injury diseases. Astragaloside IV (AS-IV) is widely used in the antiapoptotic therapy of brain injury diseases. However, its mechanism of action is still not fully understood. In this study, we investigated the effect of AS-IV on hypoxia-induced oxidative stress and apoptosis in hippocampal neurons and explored its possible mechanism. In vivo, mice were placed in a hypoxic circulatory device containing 10% O2 and gavaged with AS-IV (60 and 120 mg/kg/d) for 4 weeks. In vitro, mouse hippocampal neuronal cells (HT22) were treated with hypoxia (1% O2) for 24 hours in the presence or absence of AS-IV, MDL-28170 (calpain-1 inhibitor), or YC-1 (HIF-1α inhibitor). The protective effect of AS-IV on brain injury was further explored by examining calpain-1 knockout mice. The results showed that hypoxia induced damage to hippocampal neurons, impaired spatial learning and memory abilities, and increased oxidative stress and apoptosis. Treatment with AS-IV or calpain-1 knockout improved the damage to hippocampal neurons and spatial learning and memory, attenuated oxidative stress and inhibited cell apoptosis. These changes were verified in HT22 cells. Overexpression of calpain-1 abolished the improvement of AS-IV on apoptosis and oxidative stress. In addition, the effects of AS-IV were accompanied by decreased calpain-1 and HIF-1α expression, and YC-1 showed a similar effect as AS-IV on calpain-1 and caspase-3 expression. In conclusion, this study demonstrates that AS-IV can downregulate the calpain-1/HIF-1α/caspase-3 pathway and inhibit oxidative stress and apoptosis of hippocampal neurons induced by hypoxia, which provides new ideas for studying the antiapoptotic activity of AS-IV.